A Comparative Study Regarding Online and Offline Educational Learning Method on Second Year And Third Year Basic B.Sc. Nursing Students in Selected College (International Journal of Nursing Education, 2022)
Background: The sudden outbreak of COVID 19 pandemic shook the entire world and this situation challengedthe education system across the world which forced the educators to shift to an online mode of teaching overnight.However the effective use of online leaning method in nursing field is unknown. Methods: A comparativesurvey research design was used. The sample for the study were second and third year Basic B. Sc. Nursingstudents. A 5 point Likert scale was used to collect the comparative data. Purposive sampling technique wasused to collect the data from 62 students. Results: For online educational learning method: 36.33% stronglyagree, 11% agree, 38.22% neutral, 12% disagree, 3.5% strongly disagree. For offline educational learning method:42.36% strongly agree, 1.18% agree, 16.02% neutral, 39.89% disagree, 0.10% strongly disagree. Conclusion: Theconclusion drawn from the findings of the study is that offline learning method is better than online learningmethod according to second and third year Basic B. Sc. Nursing students.
Keywords: Online, offline, educational learning method